A framework of factors to improve ethics in the Malaysian construction industry / Norsiah Mohamad - Norsiah, Mohamad (2012)
Construction industry is one of the largest and most valuable industries in Malaysia. However, in the face of its size and universality, it is often cited as plagued with graft and unethical practices. Hence, there is a need to address the increasing concern of unethical practices or ethical issues in the industry, which necessitates a research to overcome the problems prevailing in the industry. Therefore, the aim of the research is to develop a framework of factors to improve ethics in the construction industry.